“I work for the Fleurs-de-Lis” – Multiplying the ‘Two Solitudes’ and avant la lettre Canadianness in Frontier - McPherson, Annika (Études canadiennes / Canadian Studies, 2020)
The historical drama TV series Frontier is driven by an ambiguous imaginary of Northern North America in the late 1700s. It portrays English, Irish, Scottish, French and U.S.-American settlers variously cooperating with and instrumentalizing Indigenous nations in order to undermine the Hudson’s Bay Company’s fur trading monopoly. Through devices such as the episodes’ epigraphs and in its depiction of First Nations and Black characters, the series speaks to current debates and ongoing controversies surrounding the representation of Canadianness beyond the “two solitudes”. This paper analyzes how Frontier multiplies the “solitudes” in its re-imagination of the fur trade through various lines of interaction and conflict. La série Frontier est un drame historique inspiré d’un imaginaire ambigu de l’Amérique du Nord à la fin des années 1700. La série met en scène des colonisateurs anglais, irlandais, écossais, français et américains qui coopèrent avec des nations autochtones et les instrumentalisent pour saper le monopole du commerce des fourrures de la Compagnie de la Baie d’Hudson. À travers des épigraphes et des représentations des personnages afro-canadiens ainsi que des Premières Nations, la série engendre des débats et controverses sur la représentation de l’identité canadienne au-delà des « deux solitudes ». Cet article analyse comment la série Frontier cherche à multiplier « les solitudes » à travers une chaîne d’interactions et de conflits.